Athletes' use of analgesics is related to doping attitudes, competitive anxiety, and situational opportunity - Melzer, M.; Elbe, A.-M.; Strahler, K. (Frontiers in Sports and Active Living, 2022)
This study aimed to investigate athletes' hypothetical use of non-steroidal anti-inflammatory drugs (NSAIDs), a behavior similar to doping, and its association with doping attitudes, competitive anxiety and situational opportunity. One hundred twenty-two sport science students completed an online survey assessing biographical information, doping attitudes, and competitive anxiety. Students' intention to use analgesics was measured via two different hypothetical situations using the vignette technique. The favorable situation included an absence of potential witnesses and presence of an attractive good whereas witnesses were present in the unfavorable situation and an attractive goal was absent. The results of two hierarchical multiple regression models showed that doping attitudes and competitive anxiety, especially worry, predicted the use of analgesics. In the situation featuring a favorable opportunity, worry was the strongest predictor, whereas in the situation of an unfavorable opportunity, doping attitudes was the strongest predictor for using NSAIDs. Results indicate that NSAID use is associated with positive attitudes toward doping and competitive anxiety, and that it is situationally dependent. Future research perspectives and practical implications are discussed.